PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI VARIABEL INTERVENING SEMANGAT KERJA PADA BANK PUNDI PROVINSI RIAU - Anuar, Saiful (Eko dan Bisnis: Riau Economic and Business Review, 2017)
The Effect of Leadership and Motivation toward Employer Performance through Intervening Variable of Working Spirit at Pundi Bank-Riau Province. The background in this research was focused on the low of employers’ performance at Pundi bank in Riau Province. The purpose in this research were to know the effect of leadership toward working spirit, motivation toward working spirit, leadership toward employers’ performance, motivation toward employers’ performance, working spirit toward employers’ performance at Pundi Bank-Riau Province. This research used survey design, were the research sample was the employers of Indonesia Pundi Bank Tbk Company in Riau Province which located on Pekanbaru, Bengkalis Regency, Kuantan Singingi Regency and Indragiri hulu Regency. There were 149 respondents and the data collected by questionnaire and analyzed by using ….. Analysis. The research findings showed that leadership gave positive influence and significant toward working spirit; motivation gave positive influence toward working spirit; that leadership doesn`t give positive influence and significant toward performance; motivation gave positive influence toward performance; working spirit gave positive influence toward performance. Leadership variable was the best variable which influenced employers’ performance